Enhanced electrocatalytic performance of aluminium metal-organic framework towards the detection of broad-spectrum chloramphenicol antibiotic. (1st April 2023) - Rafi, Jithin; Rajan, Aswathy; Neppolian, B.
Highlights: Electrochemical applications of Al MOF (DUT-4) were studied for the first time. DUT-4@rGO composite prepared via facile in situ solvothermal method. rGO enhances the conductivity of MOF facilitating better electrocatalytic activity. CAP was detected in a wide linear range of 1–1000 µM with an LOD of 76.97 nM. The sensor showed excellent selectivity and applicability in real water samples. Abstract: Metal-organic frameworks have gained prodigious significance in recent decades due to a wide variety of applications owing to their diverse structures, tunable porosity and large surface areas. Herein, a nontoxic Aluminium based metal-organic framework, (DUT-4) was used for the very first time for electrochemical detection of chloramphenicol (CAP), a widely used broad-spectrum antibiotic. The improper usage of CAP and its adverse effects on human beings necessitates its selective and sensitive detection. DUT-4 was synthesized by a facile solvothermal method and reduced graphene oxide (rGO) was incorporated in-situ by one-pot synthesis which enhanced its electrocatalytic activity. The as-prepared electrocatalyst was fabricated over a glassy carbon electrode (DUT-4@rGO/GCE) by a simple drop-casting technique and used for the detection of CAP. It exhibited a good current response towards the voltammetric detection of CAP in a wide linear range from 1 to 1000 µM with a very low detection limit (LOD) of 76.97 nM. A mixed mechanism of both adsorption and diffusion-controlled behaviour was evidenced in the scan rate studies. The modified electrode showed better selectivity, stability and repeatability towards CAP sensing. Moreover, DUT-4@rGO/GCE was tested in real samples including lake water and tap water with a good recovery. Graphical abstract: Image, graphical abstract